2016
DOI: 10.1007/s00170-016-9055-9
|View full text |Cite
|
Sign up to set email alerts
|

The multi-objective optimization of the loading paths for T-shape tube hydroforming using adaptive support vector regression

Abstract: The objective of this study is to introduce adaptive support vector regression, whose accuracy and efficiency are illustrated through a numerical example, to determine the Pareto optimal solution set for T-shape tube hydroforming process. A validated finite element model developed by the explicit finite element code LS-DYNA is used to conduct virtual T-shape tube hydroforming experiments. Multiobjective optimization problem considering contact area between the tube and counter punch, maximum thinning ratio, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…The errors between the predicted and the numerical results for the BH and TR were approximately -4.3% and 9.1%, respectively. These errors are within reasonable tolerances (±10 %) indicating that the RSM models can be used to predict the objectives effectively [6].…”
Section: Analysis Of Variance (Anova) and Establishing Rsm Modelsupporting
confidence: 52%
See 2 more Smart Citations
“…The errors between the predicted and the numerical results for the BH and TR were approximately -4.3% and 9.1%, respectively. These errors are within reasonable tolerances (±10 %) indicating that the RSM models can be used to predict the objectives effectively [6].…”
Section: Analysis Of Variance (Anova) and Establishing Rsm Modelsupporting
confidence: 52%
“…Furthermore, the structural stiffness and stability of the parts can also be improved through THF [4]. Hence, several reports have explored the use of THF method in the production of T-and Y-shaped tubes [5][6][7]. In THF process, bursting is generally one of the main defects due to excessive thinning of the tubes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Response variables selected in their study were thinning and protrusion height and the best optimal combination of parameters were attained by the considered method. In another work, the authors considered the contact pressure of tube and counter punch as an additional parameter along with thinning ratio and protrusion height were considered to formulate the multi-objective problem [18]. Chebbah and Leebal [19] developed a new surrogate model to optimize the parameters like thinning variation and also the industrial requirements.…”
Section: Introductionmentioning
confidence: 99%
“…To improve tube formability in THF processes, researchers applied several techniques to reduce thinning of the tube wall and to increase the possible height of the emerging branch. Huang et al [12] used the adaptive support vector regression during the T-shaped THF process to optimize the loading path. In a different research, Hwang et al [13] suggested a control algorithm to identify suitable loading paths in the T-shaped THF process with various outlet diameters.…”
Section: Introductionmentioning
confidence: 99%